The cultural practice of decluttering as household work and its potentials for sustainable consumption - Muster, Viola; Iran, Samira; Münsch, Marlene (Frontiers in Sustainability, 2022)
Popular literature and guidebooks on minimalism and decluttering have brought the idea of “less is more” into the mainstream. Although decluttering constitutes a central household chore in consumer societies, it is rarely communicated as work within the current popular minimalism discourse, but rather as an expression of self-care. Whether and to what extent this “lifestyle minimalism” can contribute to sustainable consumption has – with a few exceptions – not yet been studied in detail. In this article, decluttering is first conceptualized in between housework and self-care. Based on this work, potentials (e.g. reflection of consumption of goods and underlying needs) and limits (e.g. no focus on particularly environmentally relevant consumption areas, stimulation of new consumption) for the promotion of sustainable consumption are outlined. Finally, initial first insights from an ongoing citizen science project on decluttering in Germany are presented. The first qualitative results from two workshops and two reflection exercises show that the main motivation for participants is the dissatisfaction with their multitude of possessions and the desire for fewer material possessions in the future. The decision to declutter can be understood as a window of opportunity in which individuals are willing to reflect on and realign their possessions and desires for goods. Thus, we argue that decluttering can be a relevant starting point for changing consumption behavior towards (more) sustainable consumption. At the same time, it remains unclear whether and to what extent the participants' willingness to change with regard to regarding possessions and consumption actually leads to more sustainable consumption behavior after decluttering. It is even conceivable that the newly gained space will stimulate additional consumption. Decluttering would then rather function as a catalyst for further consumption (and would have no or rather a negative contribution to sustainability goals). Further research is needed to shed light on this.